Two-year follow-up study of membranous nephropathy treated with tacrolimus and corticosteroids versus cyclical corticosteroids and cyclophosphamide - Ramachandran, R; Yadav, A; Kumar, V; Siva Tez Pinnamaneni, V; Nada, R; Ghosh, R; Kumar, V; Rathi, M; Kohli, H; Gupta, K; Sakhuja, V; Jha, V (Elsevier, 2017)
Introduction Both cCTX/GCs and CNIs are recommended as first-line agents in the management of PMN. The present study is an extended report of patients randomized to receive TAC/GCs or cCTX/GCs at 2 years post randomization. Methods Seventy patients enrolled in the clinical trial Tacrolimus Combined With Corticosteroids Versus Modified Ponticelli Regimen in Treatment of Idiopathic Membranous Nephropathy: Randomized Control Trial were followed quarterly between 12 and 24 months. At the end of 24 months, 3 patients were lost to follow-up. Results At 18 months, 66% and 89% (P = 0.04) were in remission in TAC/GCs and cCTX/GCs groups, respectively. At 18 and 24 months, 60% and 86% (P ¼ 0.03) of cases were in remission in the TAC/GCs and cCTX/GCs groups, respectively. At 18 months, 57% and 83% (P = 0.03) of the patients in TAC/GCs and cCTX/GCs groups were in remission without need of any additional immunosuppression (persistent remission) and, at 24 months, 43% and 80% (P = 0.002) were in persistent remission in TAC/GCs and cCTX/GCs groups, respectively. Relapse rate after any remission was 40% and 6.7% in TAC/GCs and cCTX/GCs groups, respectively (P = 0.007). There was an association of aPLA2R titers with remission or resistance (P = 0.006) in relapsing PMN. The significant decrease in eGFR after 12 months of TAC/GCs therapy normalized at 18 and 24 months. Discussion At 2 years after randomization, relapse rates are higher for TAC/GCs compared with cCTX/GCs in PMN patients. Thus, cCTX/GCs are better than TAC/GCs in the longer term in PMN patients.